Control of multiphase evolution and Al-deficiency in reactive-sintered MoAlB ceramics with excessive Al. Issue 13 (October 2022) - Zhang, Zhi-Kun; Gu, Hui; Sun, Dong-Dong; Bai, Yue-Lei; Hu, Chun-Feng
Abstract: MoAlB is a ternary boride of MAB phases with strong resistance to oxidation and ablation at service temperature, thanks to preferential Al diffusion to form a protective oxide scale. However, excessive Al were often necessary in sintering of MoAlB ceramics, suggesting that a liquid-phase densification might occur thus leading to complex microstructures. By quantitative SEM analysis, 17 mol.% Al2 O3 phase was found common in MoAlB ceramics. The liquid-phase of Al-Mo-B-O facilitates the direct conversion from MoB to MoAlB before in situ formation of Al2 O3 . An intermediate Mo3 Al8 phase competes with layered conversion, which limits the insertion rate of Al into B-B layers of MoB to form abundant Al-deficient stacking-faults. Intermetallic Mo3 Al8 phase precipitates further in the intergranular regions parallel to the crystallization of Al2 O3, leaving the reprecipitation of remaining Al. Both layered-conversion and intergranular oxides can improve ablation behavior for MoAlB ceramics, as well as fracture toughness and compressive strength. Graphical Abstract: ga1